(untitled) (International Journal of Physiotherapy, 2018)
Background: Chronic LBP a frequent sign of back dysfunction. The recent literature recorded that up to 90% of the world’s population complain from LBP which cause disability in people. This study conducted to compare the efficacy of aquatic and conventional therapy on pain level, functional limitation and lumbar ROM in subjects with CLBP. Methods: Forty CLBP were divided into two groups (A) control 20 subjects received conventional therapy. (B) experimental received 20 subjects received aquatic therapy the treatment was given for six weeks. Results: Mixed MANOVA test showed statistically significant enhancement in values of post-treatment in either group compared with pre-treatment in pain enhancement for group A was 54.86% and 57.74% for group B (P=0.0001), functional limitation enhancement for group A was 55.46% and 58.95% for group B (p=0.0001), and lumbar ROM enhancement for group A was 46.63%, 18.79%, for lumbar flexion, and extension, and for group B was 46.96%, 22.85% (p=0.0001). Conclusion: It is concluded that aquatic and conventional therapies have a similar result in reducing pain severity, functional limitation, and enhancing lumbar ROM in CLBP patients.